The new millennium workplace: seven changes that will challenge managers—and workers. - Barner, Robert (Futurist)
Seven trends that the writer believes will reshape work environments over the next decade are discussed. They are the virtual organization, the growth of which is being fueled by the rapid evolution of electronic technologies, the rapid spread of computer networks, and the growth of telecommuting; an expanded temporary workforce; the ascendancy of knowledge workers; computerized coaching and electronic monitoring; the growth of worker diversity; the aging of the workforce; and the birth of the dynamic workforce, one that recognizes the need for continuous improvement to meet changing customer requirements and competitor actions. Six survival skills for the so-called protean manager—one who is flexible and adaptive enough to survive in an ever-changing environment—are also presented.